Impact Analysis of Hydration and Sleep Intervention Using Regression Techniques (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
"Health is Wealth,"- The most well-known golden maxim, but most of the time, we ignore our health in favor of our professional pursuits. Good health covers not just our physical but also our psychological well-being. Individuals have forgotten that preserving our wellbeing contributes a large amount of effort to our advancement in this growing-race. Individuals agree that juggling the demands of life in clinical medicine poses a unique challenge, but good health can be sustained by drinking plenty of water and sleeping enough. We conducted an online questionnaire survey with a total of 30 questions, and the data gathered will be used to continue our hypotheses. Our main goal in this study will be to focus on the significance of drinking water and sleep respective to their age using machine learning regression algorithms. Therefore, a corrective statistical analysis can be predicted based on a dependent and independent variable.